Staying with the violence: reflections on traveller violence(s), multi-perspectivism, and raw ethnography - Howarth, Anthony (Gender and violence in Romani and Traveller lives, 2025)
Employing the term "raw ethnography" this chapter seeks to reimagine violence beyond oppressor/oppressed binaries and to unsettle gender-based distinctions regarding violence's localisation. Drawing on ethnographic descriptions of a bare-knuckle boxing match between Traveller men, and of combat between two women, violence is examined in ways that trouble previous approaches. In these examples, violence erupts from young men's blaggarding, from the confines of family life, or because of intra-family conflicts. It is suggested that enactments of Traveller violence, whether perpetration or victimhood, emerge from spaces that are not simply brutal but virtuous. Gregory Bateson's notion of schismogenesis is combined with the authors method of multi-perspectivism to examine violences productive value, its blood-curdling repugnance, and much that lies between.